POLA KOMUNIKASI ISLAM DALAM PEMBELAJARAN (Suatu Analisis Psikologi Pendidikan) - Authar, Tanzil; Warul Walidin; Syabuddin; Salami Mahmud (STIT Muhammadiyah Aceh Barat Daya, 2024)
The Quran does not specifically discuss Islamic communication practices. Islamic communication, typified by Qaulan, primarily revolves on interpersonal relationships. It involves linguistic interactions that are influenced by context and circumstances. The study employs qualitative methodologies. Research refers to the process of doing library research by analyzing material, such as written texts, notes, or reports, in order to provide novel research discoveries. Analytical terms are used to scrutinize information conveyed via symbols recorded in diverse media, including books, articles, and other mediums. The word